The association of depression, risky sexual behaviours and herpes simplex virus type 2 in adults in NHANES, 2005–2008. Issue 1 (5th November 2011) - Pratt, L A; Xu, F; McQuillan, G M; Robitz, R
Abstract : Objectives: Depression has been linked to risky sexual behaviours in adolescents, but there is little research among adults. The goal of this analysis was to examine the associations between current depression and self-reported risky sexual behaviours in a nationally representative sample of US adults aged 20–59 years. The authors also examined the association between depression and infection with herpes simplex virus type 2 (HSV-2), a biological marker of risky sexual behaviours. Methods: The authors used data from the 2005–2008 National Health and Nutrition Examination Surveys. Current depression was measured by the Patient Health Questionnaire-9. Antibodies to HSV-2 were tested using the enzymatic immunodot assay. The authors used logistic regression to examine the associations controlling for socio-demographic variables. Results: Among 5273 adults aged 20–59 years, 7% had depression, 36% reported 10 or more lifetime sex partners, 15% had two or more past-year sex partners and 13% had first sex before 15 years of age. Persons with each of the risky sexual behaviours were more likely to have depression than those without. In stratified analyses, risky sexual behaviours were associated with depression in women but not in men. Among 3940 adults aged 20–49 years, 19% had HSV-2 infection. Persons with HSV-2 infection were more likely to have depression (OR 2.1, 95% CI 1.5 to 2.9). Conclusions: Risky sexual behaviour is related to current depression in adult women. Healthcare providers should be aware of this association and its potential implications in order to deliver better care for patients with depression or sexually transmitted infections.